By 'trial and error': A report on a national survey on the situation and perceptions of court interpreters in Malaysia - Zubaidah Ibrahim (Journal of Modern Languages)
This paper is derived from a lengthier report (Zubaidah 1999) submitted to the Chief Registrar of the Federal Court and to the University of Malaya Research and Development Unit in 1999, whose assistance which is gratefully acknowledged enabled the research to be conducted. It presents the results of a survey of the Malaysian Court Interpreter Service, based on a 54-item postal questionnaire which supplies information on the interpreters - as individuals and as a group - set in the career context of the bilingual service provider: a kind of snapshot of all 566 serving Court Interpreters in Malaysia in mid-1998.